Okara-enriched fermented sorghum instant porridge: effects on mineral bioaccessibility and structural properties - Adeyanju, Adeyemi Ayotunde; Adebo, Oluwafemi Ayodeji (Frontiers in Nutrition, 2025)
This study investigated the impact of okara inclusion and fermentation on bioaccessible minerals and structural properties of sorghum-based instant porridges. Fermented and unfermented porridges were formulated using sorghum, okara, and their blends (70:30 and 50:50). Mineral composition and bioaccessibility, as well as structural characterization, including scanning electron microscopy (SEM), X-ray diffraction (XRD), and Fourier transform infrared spectroscopy (FTIR), were analyzed. Okara inclusion elevated Fe and Zn contents, while fermentation improved their bioaccessibility. Blends with okara were richer in iron than their 100% sorghum counterparts by approximately 6–9% and 15–47% for fermented and unfermented porridge samples, respectively. Bioaccessible Fe increased by up to 194%, and Zn reached 32% compared to sorghum-only porridges. SEM revealed gelatinization and enzymatic breakdown, while XRD and FTIR confirmed altered starch crystallinity and molecular interactions. Specifically the FTIR spectra showed that the amide I and amide II bands, approximately 1,642 cm−1 and 1,513 cm−1, associated with C=O stretching and N–H bending of proteins, respectively, were stronger in porridge samples containing okara, which aligns with its higher protein content compared to sorghum These results highlight the potential of okara-fortified fermented sorghum porridge to deliver improved nutrition and foster circular food systems by transforming an agro-industrial by-product into a valuable ingredient.